The impact of regional political developments on the evolution of transnational terrorism in Saudi Arabia - Alsubaie, Saad Ali (Kansas State University, 2012)
Since the late 1970s Saudi Arabia has experienced transnational terrorism in sporadic waves whose character has evolved over time. While most of the literature on these waves of terrorism focuses on religious extremism this dissertation argues that terrorism in Saudi Arabia, although framed in religious terms, is not the result of religious factors alone, but more importantly a function of external variables. Taking the role of religious extremism into consideration, this dissertation underlines the importance of external factors on the mobilization of transnational terrorist groups throughout the Islamic world and particularly in Saudi Arabia. It argues that religious extremist terrorism cannot be examined in isolation from the context of the developments that ignite it and revolutionize its doctrine. This dissertation examines three key regional political developments – the Iranian revolution, the 1990 Gulf war, and the 2003 Iraq war – together with terrorist violence in their aftermath to show how the significant political events transformed extremist worldviews from passive to violent to organized terrorism. Though the character of these three political events and the terrorist acts that they unleashed differ widely in context, scope, and character, there are common threads among all three that illuminate how different dynamics contribute to the evolution of transnational terrorist mobilization. The dissertation identifies how the development of a politico-religious ideology, shaped and revolutionized by the presence of political crises, became a driving force behind much of the terrorism following these major political events. By exploring the interplay of popular perceptions, political entrepreneurs, and state responses, this dissertation seeks to better understand the complex dynamics involved in the evolution of transnational terrorism in Saudi Arabia.
Keywords: Terrorism; Religion; Saudi Arabia; Islam; Transnational terrorism; Politico-religious ideology; History (0578); Political Science (0615)